Alih Kode Pada Anime Great Pretender Karya Ryota Kosawa - Febri, Nada Fadiya; Putri, Meira Anggia (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
Code-switching involves the transition between different language varieties or between different languages. This phenomenon occurs in anime, particularly in the anime "Great Pretender." The anime's appeal lies in its characters frequently code-switching within the same conversation. Finding the factors that affect code-switching in "Great Pretender" is the study’s main purpose. The study used method in the form of descriptive through a qualitative approach to collect data in tangible of code-switching dialogues using techniques of observation and note-taking. The approach of intralingual matching is used to analyze the data. 10 examples of code-switching between the Japanese and English languages are found as a consequence of the investigation. 4 elements contribute to the use of code-switching in the anime "Great Pretender": (a) the speaker or interlocutor, (b) the listener or conversational partner, (c) change in situasion due to the presence of a third person, and (d) change of topic of conversation.